The Strategic Role of Content Marketing and Innovation in Influencing Consumer Purchase Decisions at JN Collection - Irvan Rolyesh Situmoranga; Vinzenzo Yawrent (Lembaga Riset dan Inovasi Al-Matani, 2025)
This research was conducted at JN Collection. The purpose of this study was to determine and analyse the influence of content marketing and innovation on purchasing decisions. The population and sample of this study were 74 customers. The sampling technique used was saturated sampling. The data collection technique was a questionnaire. Data analysis was conducted using multiple linear regression analysis. The results of the study found that Content Marketing has a positive and significant influence on Purchasing Decisions at JN Collection, Innovation has a positive and significant influence on Purchasing Decisions at JN Collection, and Content Marketing and Innovation have a positive and significant influence on Purchasing Decisions at JN Collection. The conclusion of this study is that an increase in content marketing and innovation can drive an increase in purchasing decisions.